Late bedtime is associated with decreased hippocampal volume in young healthy subjects. Issue 1 (8th September 2014) - Kuperczkó, Diána; Perlaki, Gábor; Faludi, Béla; Orsi, Gergely; Altbacker, Anna; Kovács, Norbert; Dóczi, Tamás; Komoly, Sámuel; Schwarcz, Attila; Clemens, Zsófia; Janszky, József
Abstract Hippocampal volume loss has been described in several pathological conditions including sleep disorders. Whether differences in normal sleep are associated with differences in hippocampal volume is unknown. Here we designed a study to assess volume of the hippocampus with regard to bedtime, wake up time and sleep duration in 90 healthy university students. To assess hippocampal volumes we applied semi‐automatic user‐independent magnetic resonance volumetry. We found a significant association between delayed bedtime and smaller hippocampal volumes, a non‐significant tendency for smaller hippocampal volumes in the late wake up time group and significantly smaller hippocampal volumes for both short and long sleepers. These results suggest the importance of adequate sleep timing and especially bedtime in determining hippocampal volume.